A study on factors affecting knowledge of family planning among married women of reproductive age of Chepang community in Benighat VDC of Dhading district. - Tripathi, Prativa (2014)
ABSTRACT: This research had been under taken for the partial fulfillment of the degree of Bachelor in Nursing. The study was conducted on "Factors affecting knowledge of family planning among married women of reproductive age of Chepang community in Benighat VDC of Dhading District". The main objective of the study was to assess the factors affecting knowledge of family planning married women of reproductive of chepang community. The study design was non-experimental and study method was descriptive study. The sample of 80 married women of reproductive age of chepang community of Benighat VDC of Dhading district was selected by simple random method and primary data was collected by face to face interview method using semi structured questionnaire. Validity and reliability of the tools was maintained. Data was analyzed by using SPSS 16 version. The findings of the study were represented in frequency tables and cross tab for hypothesis testing. Major findings were 74% had inadequate knowledge level and 26% had adequate. Most of them had heard about family planning. Early marriage and teenage pregnancy was remarkably high among chepang women. Most of them had poor economic condition. Majority of the respondents were illiterate. Almost half of them (49.4 %) were present contraceptives user and 50.6% were non-user. Almost all (92.2%) had knowledge about methods of FP. Educational status Present contraceptives user and income affects the knowledge of family planning. The main reason for non-use of the contraceptives were family objections, feel uneasy to go to service center, lack of husband support and inaccessible. Almost all chepang women are engaged inside the house. Spousal communication was very poor in chepang community. Majority of the respondents had more than 4 numbers of children. The major occupation for the livelihood in chepang community is agriculture. The educational status of the respondents and income affects the knowledge of the family planning (p = 0.002 and p = 0.014) respectively. It is found that more research needs to be done in large scale among chepangs. Female education should be promoted. Various awareness programs should be conducted locally for the increase utilization of the FP.